Dano foliar por insetos em Sapucaias (Lecythis pisonis): coloração da folha como defesa anti-herbivoria? - Susan Vieira Gomes (2022)
Herbivory is an ecological interaction characterized by the consumption of plant tissue by animals. Among the most diverse animals on the planet are insects, which are abundant in both natural and urban environments, acting as predators, pollinators, decomposers, and herbivores in these places. Herbivory by insects is modulated by the presence of physical and chemical plant defenses, which act to prevent or discourage the attack. Studies have linked color change along leaf ontogeny to changes in defense strategies against herbivory, however, few studies have related herbivory to leaf coloration. Sapucaias (Lecythis pisonis) are arboreal plants that present leaf budding and flowering in September in southeastern Brazil. It presents a remarkable feature for studying temporal patterns of herbivory since its young leaves are pink and turn green with the advancing of the wet season. Previous studies in other plant-herbivore systems indicate a relationship between the red color, given by the presence of anthocyanins, and leaf tannins. This relationship may suggest that leaf coloration, when young, may be an anti-herbivory defense signal for insects. The objective of this research was to evaluate insect herbivory and leaf defense in sapucaia trees, taking into account leaf coloration in the month of budbreak and temporally throughout the rainy season in a tropical city in Brazil. Young pink leaves exhibited smaller leaf area and greater specific leaf area compared to green leaves in the month of budbreak, indicating that young pink leaves may be more susceptible to herbivory than green leaves due to this lower physical defense. However, there was no difference in leaf herbivory by insects between green and pink leaves in the budding month, with an average of 4.6% of leaf area lost and 3.7% of leaves attacked in September, considering all leaf colorations. Throughout the rainy season, from October to March, no significant differences were found in herbivory, which was, on average, 4.5% of leaf area removed and 9.3% of the frequency of leaves attacked, considering all months. The leaf area consumed by insects between September and March was similar, however, the number of leaves attacked in September was significantly lower when compared to October and subsequent months of the rainy season. Despite the similarity in leaf herbivory found in the leaves of different colors in the first month, there may be defense mechanisms (chemical-visual or mechanical) as after the color changes in leaves there is an increase in the number of attacked leaves. Another possibility is that with the change of season (dry to rainy) there is an increase in the abundance and activity of herbivores causing an increase in the frequency of attacked leaves. Future research may elucidate whether there is a relationship between leaf pigments and levels of chemical and/or mechanical defense against herbivory in sapucaias and whether there are changes in leaf defense throughout their ontogeny. Finally, we suggest an alternative hypothesis to explain the presence of pink leaf color in young leaves in sapucaias, here called the "pollinator attraction display" hypothesis.